Strategic Innovation Roadmapping in the Age of AI: A Framework for Competitive Advantage - Pasa, Inda Tri; Andrianto, Deny Tomy (Indonesian Scientific Publication, 2025)
This study investigates how the quality of innovation roadmaps, moderated by organizational AI readiness and strategic maturity, shapes competitive advantage. Unlike prior studies that focus on either digital maturity or AI adoption alone, this research emphasizes the structural integrity of roadmaps clarity, adaptability, and alignment as a distinct driver of innovation performance in rapidly evolving technological environments. Methodologically, the study applies a conceptual–empirical design using 2023–2024 industry benchmarks and sector-neutral indicators. Anchored in the Dynamic Capabilities Theory and Resource-Based View, it hypothesizes that high-quality roadmaps, when mediated by AI readiness, accelerate time-to-market and enhance return on investment (ROI). Findings indicate that organizations employing digitally supported, high-quality roadmaps achieve up to 30% higher project success rates and 25% faster innovation cycles. Yet, these benefits are conditional realized only where infrastructure maturity, inclusive governance, and supportive policy frameworks exist. Persistent barriers, including organizational resistance, fragmented data systems, and regulatory complexity, constrain the broader realization of these outcomes. The study concludes that strategic roadmapping is most effective when framed as a systemic integration of tools, people, and policies. Its primary contribution is a scalable framework that aligns innovation planning with digital capability, offering firms both agility and resilience to sustain competitive advantage in volatile markets.